Determinants of Customer Satisfaction in Mobile Banking: a PLS Analysis of DG Bankaltimtara Application Users - Santika, Sisca; Putri Shafar, Habibah; Kusno, Hendra Sanjaya (International Journal of Business, Law, and Education, 2024)
This study was conducted with the aim to determine and analyze the effect of using DG Bankaltimtara mobile banking application on Customer Satisfaction of PT East Kalimantan and North Kalimantan Regional Development Bank Balikpapan Branch Office. The population in this research is 15,960 customers who use DG Bankaltimtara. Researchers took a sample based on the Slovin formula of 390 respondents. The type of data used is primary data sourced from questionnaires presented in the form of a Likert scale. Data analysis in this study used descriptive analysis methods with the help of the Partial Least Square (PLS) application with the SmartPLS version 3.0 program. The results of this study were obtained using the PLS Evaluation Model to show the effect of using the DG Bankaltimtara Mobile Banking Application on Customer Satisfaction. Ease of Service Users, Credibility of Banking Service Companies, and Transaction Speed are three variables that affect Customer Satisfaction in using Mobile Banking DG Bankaltimtara. However, the System Security variable has no effect on Customer Satisfaction in using Mobile Banking DG Bankaltimtara.